A population-based study of the epidemiology of oral squamous cell carcinoma in the Netherlands 1989–2018, with emphasis on young adults. Issue 1 (January 2022) - Al-Jamaei, A.A.H.; van Dijk, B.A.C.; Helder, M.N.; Forouzanfar, T.; Leemans, C.R.; de Visscher, J.G.A.M
Abstract: There has been an increasing trend in oral squamous cell carcinoma (OSCC) in patients under 45 years of age. The aim of this study was to evaluate the burden of OSCC in the Netherlands between 1989 and 2018 among young adults (age 20–34 years) when compared to adults (age 35–44 years), and to describe the burden in older groups as well, utilizing cancer registry data to characterize incidence patterns by age, sex, and risk factors. A total of 18, 963 cases of OSCC were reported. The overall incidence rate, as measured by annual percentage change (APC), increased significantly from 1989 to 2010 by 1.3% per year (95% confidence interval (CI) 0.9–1.7%) but decreased thereafter by −0.9% (95% CI −2.5% to 0.7%). Annual incidence increased significantly by 2.4% (95% CI 1.1–3.8%) for patients aged 20–34 years, while it decreased for those aged 35–44 years by −0.9% (95% CI −1.7% to 0.0%). In patients older than 60 years, incidence rates increased overall (60–74 years: APC 1.8%, 95% CI 1.5–2.1%; ≥75 years: APC 1.5%, 95% CI 1.2–1.9%). Overall, 66.5% of patients were smokers and 65.3% were alcohol consumers. The marked differences in incidence within the young age subgroups warrants further investigation to elucidate any likely disparity in biological process and clinical outcomes in these populations.